ORGANIZATION AND PLANNING OF THE EDUCATIONAL PROCESS IN THE CREDIT-MODULE SYSTEM - Pardaboyev Otkir Abduraхimovich (International Scientific and Current Research Conferences, 2023)
The European system of credit distribution developed, tested and improved by 45 European countries; credit-module system of education - a model of organization of the educational process implemented in the unit of modular education technologies and ECTS test credits. Academic mobility is the going of students of a higher education institution for a certain period of time to study at another higher education institution in the territory of the republic or abroad.